Cyclic Imine-BF3 Complexes as Precursors for Functionalized Azacycles - Bhatt, Kamal; Seidel, Daniel (Synlett, 2025)
Due to the relative instability and low electrophilicity of enolizable alicyclic imines, their functionalization commonly requires cryogenic temperatures and highly reactive nucleophiles such as organolithium compounds. Stable BF3 adducts of these imines streamline the synthesis of functionalized amines and obviate the need for cryogenic temperatures. In favorable cases, these adducts can be stored for over a year. The compatibility of cyclic imine-BF3 complexes with organometallic and radical-centered nucleophiles makes them ideal building blocks for functionalized azacycles.1 Introduction2 Synthesis of Cyclic Imine-BF3 Complexes3 Reactions of Imine-BF3 Complexes with Organometallic Nucleophiles4 Radical Additions to Imine-BF3 Complexes5 Conclusions
Keywords: imine-BF3 complexes; alicyclic amines; acridines; photocatalysis; radical additions